Starches (Eagan Press, 1999)
Starches is the fifth title in the Eagan Press Handbook Series. Combining a user-friendly format with expert guidance, handbooks in this series are designed to meet the needs of professionals in many areas of the food industry. Each title focuses on an ingredient or application, giving information that is currently unavailable in a single source and presenting its subject in straightforward language.